Measurement of the degree of consumer satisfaction in function of market quality indicators: a preliminary Analysis (Research, Society and Development, 2019)
Faced with a scenario so competitive, the expansion of business of an organization is given by differentiating and stability in relations with customers. For a company different from the other, it must be able to satisfy and retain customers. The main objective of the research was to identify the degree of satisfaction of customers using market quality indicators. The research is characterized as described and the methodological process took place with the application of questionnaires online, from the use of a free platform. 90 questionnaires were applied simultaneously. The metric used is based on the adaptation of the Likert scale, inferring the degree of satisfaction for flatness. The data was tabulated and, therefore, simplified graphics generated using Excel tool. Among the results, if the quality of the products and services offered as the greatest significance, because 80% of respondents believe that this indicator is paramount to guarantee the sense of customer satisfaction. Therefore, companies must pay attention to indicators that interfere directly in satisfaction of its customers, especially when customer satisfaction varies greatly depending on the type of service provided.